Cloud Infrastructure for Car Service - Litvinova, E. I.; Englesy, I. P; Miz, V. A; Shcherbin, D. (EWDTS, 2013)
A set of innovative scientific and technological solutions, including for solving social, human, economic and environmental problems associated with creation and use of a cloud for monitoring and management is developed. All of these technologies and tools are integrated into the automaton model of real-time interaction between monitoring and management clouds, vehicles and road infrastructure. Each car has a virtual model in a cyberspace - an individual cell in the cloud, which is invariant with respect to drivers of vehicles. Where does it go real cyber world? Corporate networks, personal computers, as well as individual services (software), go to the "clouds" of a cyberspace, which have an obvious tendency to partition the Internet for specialized services, Fig.1. If today 4 billion users are connected in the Internet (1 zettabytes = 7021 210 = bytes) by means of 50 billion gadgets, in five years each active user will have at least 10 devices for connecting in cyberspace. Use of personal computers without replicating data to all devices becomes impossible. But even simple copying requires more non-productive time for servicing systems and projects, which can reach 50% if several devices or servers with identical functions are available. Unprofessional (bad) service of such equipment creates problems reliable data retention, as well as unauthorized access. Also, there is a problem of remote access to the physical devices when migrating users in the space, and obtaining the necessary services and information from gadgets left at home or in the office is difficult. Economic factor of effective use of purchased applications installed in gadgets and personal computers, force the user to give up their purchase in favor of almost rent free services in the clouds. All of the above is an important argument and undeniable evidence of imminent transition or the outcome of all mankind to cyberspace of virtual networks and computers, located in reliable service clouds. Advantages of the virtual world lie in the fact that the micro-cells and macro-networks in the clouds are invariant with respect to numerous gadgets of each user or corporation. Cloud components solve almost all of the above problems of reliability, safety, service and practically don't have disadvantages. So far as the corporations and users go to the clouds, protection of information and cyber components from unauthorized access, destructive penetrations and viruses is topical and market appealing problem. It is necessary to create a reliable, testable and protected from the penetrations cyberspace infrastructure (virtual PCs and corporate networks), similar to currently available solutions in the real cyber world. Thus, each service being developed in the real world should be placed in the appropriate cloud cell that combines components similar in functionality and utility. The above applies directly to the road service, which has a digital representation in cyberspace for subsequent modeling all processes on the cloud to offer every driver quality conditions of movement, saving time and money. The goal of the project is improving the quality and safety of traffic through creating intelligent road infrastructure, including clouds of traffic monitoring and quasi-optimal motion control in real-time by using RFID-passports of vehicles, which allow minimizing the time and costs of traffic management and creating innovative scientific and technological solutions of social, humanitarian, economic and environmental problems of the world.
Keywords: Cloud Infrastructure; Car Service